UPAYA MENINGKATKAN KEAKTIFAN BELAJAR PPKN SISWA MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA SISWA SMAN 1 KUANTAN MUDIK - mirza hardian; Ardiana; Verli Novaroza (JURNAL RANDAI, 2023)
This research is classroom action research. The purpose of this research is to increase student PPKn learning activity through the application of the problem-based learning (PBL) learning model. The research subjects were students of grade 12 social studies 2 SMAN 1 Kuantan Mudik. The data collection technique used data from observation, pre-test, and post-test. The results of the research on learning activity in the pre-test (51.94%) showed 13 students whose level of activity was still low in the first cycle, increasing to (80.8%) for 18 students with high activity levels. and in the second cycle increased to (91%) 18 active students. The low activeness of Class X II IPS 2 SMA Negeri 1 Kuantan Mudik students encouraged researchers to conduct Classroom Action Research (CAR) at the SMA. This study aims to (1) find out how the use of PBL increases the learning activity of Civics Class XII IPS 2 students at SMA Negeri 1 Kuantan Mudik and (2) find out how to increase the learning activity of Civics students in Class X II IPS 2 SMA Negeri 1 Kuantan Mudik.